LASER PROSPECTS IN DENTISTRY AND MAXILLOFACIAL SURGERY - V.V. CHERNEGOV; L.V. VASILIEVA; A.A. MITROFANOV; O.V. MITROFANOVA (Avicenna Tajik State Medical University, 2020)
The biomechanical parameters of laser radiation are complex and still insufficiently studied. A great number of studies are devoted to the laser's actions on biological systems and tissues. It is considered that the findings of these studies form an almost independent field of knowledge. The major role in it plays the parts of clinical pathology. Description of action effects of laser radiation would not be considered credible without analyzing this direction. It is difficult to imagine progress in medicine without laser technologies that became modern assistants in solving many medical problems, by opening up new opportunities for us. The study of the mechanisms of action of laser radiation waves and energy levels on biological structures dictates the need for continuous improvement of laser medical multifunctional devices, the range of applications in clinical practice has become so broad that it is difficult to find a field of medicine where lasers are not used.